Estimating the contribution of key populations towards HIV transmission in South Africa. Issue 1 (2nd February 2021) - Stone, Jack; Mukandavire, Christinah; Boily, Marie‐Claude; Fraser, Hannah; Mishra, Sharmistha; Schwartz, Sheree; Rao, Amrita; Looker, Katharine J; Quaife, Matthew; Terris‐Prestholt, Fern; Marr, Alexander; Lane, Tim; et al.
Abstract: Introduction: In generalized epidemic settings, there is insufficient understanding of how the unmet HIV prevention and treatment needs of key populations (KPs), such as female sex workers (FSWs) and men who have sex with men (MSM), contribute to HIV transmission. In such settings, it is typically assumed that HIV transmission is driven by the general population. We estimated the contribution of commercial sex, sex between men, and other heterosexual partnerships to HIV transmission in South Africa (SA). Methods: We developed the "Key‐Pop Model"; a dynamic transmission model of HIV among FSWs, their clients, MSM, and the broader population in SA. The model was parameterized and calibrated using demographic, behavioural and epidemiological data from national household surveys and KP surveys. We estimated the contribution of commercial sex, sex between men and sex among heterosexual partnerships of different sub‐groups to HIV transmission over 2010 to 2019. We also estimated the efficiency (HIV infections averted per person‐year of intervention) and prevented fraction (% IA) over 10‐years from scaling‐up ART (to 81% coverage) in different sub‐populations from 2020. Results: Sex between FSWs and their paying clients, and between clients with their non‐paying partners contributed 6.9% (95% credibility interval 4.5% to 9.3%) and 41.9% (35.1% to 53.2%) of new HIV infections in SA over 2010 to 2019 respectively. Sex between low‐risk groups contributed 59.7% (47.6% to 68.5%), sex between men contributed 5.3% (2.3% to 14.1%) and sex between MSM and their female partners contributed 3.7% (1.6% to 9.8%). Going forward, the largest population‐level impact on HIV transmission can be achieved from scaling up ART to clients of FSWs (% IA = 18.2% (14.0% to 24.4%) or low‐risk individuals (% IA = 20.6% (14.7 to 27.5) over 2020 to 2030), with ART scale‐up among KPs being most efficient. Conclusions: Clients of FSWs play a fundamental role in HIV transmission in SA. Addressing the HIV prevention and treatment needs of KPs in generalized HIV epidemics is central to a comprehensive HIV response.